Implementation Method of U-Ditch Drainage Installation on M. Yamin Road in Samarinda - Pratiwi, Dheka Shara; Arfian, Iqbal; Jasman, Zaky (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2024)
Drainage channels are one of the complementary structures on road sections to meet one of the technical requirements of road infrastructure. This construction project is driven by a common issue, which is the overflow of the drainage system on M Yamin Street. This can be observed through the community's concerns about the numerous flood points occurring on that road. Infrastructure development should reach the community, especially low-income communities, while always considering spatial planning and the interconnectedness and integration with other social environments. The implementation method of the Drainage Construction Project on M Yamin Street, Samarinda City, includes the following steps: Preparatory work, Excavation Work, Piling Work, Installation of Precast U-Ditch using an excavator and a crane, U-Ditch with the dimensions of 300 x 165 x 100 cm is installed. It utilizes D16 - 200 mm and D13 - 200 mm steel reinforcement with concrete quality of Fc 30 Mpa, Reinforcement Work, formwork, Concreting Work uses concrete quality K 350 with dimensions of a width (b) of 300 cm and a thickness (t) of 30 cm. It utilizes Φ16 - 200 mm reinforcement steel and Φ13 - 200 mm support steel with a steel grade of Fy 350 MPa. Based on observations, the slump value obtained from K 350 Mpa concrete is 11.8 cm, which falls within the planned slump range for slab concrete work, ranging from 7.5 cm to 15 cm, finishing.